Evidence :law and context - Doak, Jonathan (Routledge, 2018)
Evidence: Law and Context explains the key concepts of evidence law in England and Wales clearly and concisely, set against the backdrop of the broader political and theoretical contexts. The book focuses on the essential topics commonly found on Evidence courses covering both criminal evidence and civil evidence. It takes a contextual approach discussing how wider policy debates and societal trends have impacted upon the recent evolution of the law in order to provide students with an explanation as to how and why the law has developed.